Psychological assessment and support in functional neurological disorder: a longitudinal study - Radin, Yvonne; Bulfon, Matteo; Caruso, Paola; Barbi, Egidio; Manganotti, Paolo; Clarici, Andrea (Frontiers in Psychology, 2025)
In the Department of Neuroscience in Clinical Neurological unit of our hospital, between 2020 and 2024, 58 adult patients were diagnosed with functional neurological disorder (FND). Out of these, 42 patients agreed to participate in a structured intervention consisting of 10 sessions of psychotherapy. This study aimed to investigate the demographic and clinical characteristics of the patient cohort, examine their reported symptoms, and evaluate the effectiveness and adherence to the psychotherapy program. The Affective Neuroscience Personality Scales (ANPS) were administered to assess the affective states of the patients, while the Shedler-Westen Assessment Procedure (SWAP-200) was used to evaluate their main personality style. A central objective of the research was to explore patterns or correlations between self-reported data from the patients and the evaluations completed by their therapists. This comparison sought to identify any alignment or discrepancies in the perception of symptoms and therapeutic progress, as measured by both the ANPS and SWAP-200 scales. The study’s preliminary findings are reported to provide valuable insights into the impact of psychotherapeutic interventions for FND, including an understanding of the degree to which patient self-reports correspond with clinical assessments. These results will inform the optimization of treatment strategies and enhance patient outcomes by integrating patient feedback with clinical evaluations. The research contributes to the broader knowledge of FND management, emphasizing the importance of aligning patient and therapist perspectives in the therapeutic process.